Polymicrobial detection and salivary metabolomics of children with early childhood caries - Ting Pan; YuJia Ren; JingYi Li; Ying Liao; XiangHui Xing (PeerJ)
Background Early childhood caries (ECC) has been proposed to be associated with various microorganisms and metabolites. This study aims to compare the prevalence of specific microbial species and salivary metabolomics profile in children with and without ECC, and to explore the correlation between salivary metabolites and targeted microbes. Method Five ml of unstimulated saliva was collected from 32 ECC and 22 caries-free children. Clinical indexed were recorded and questionnaires regarding oral health and dietary habits were obtained from the guardians. The presence of eight specific microbial species were examined using species-specific quantitative PCR (qPCR). Untargeted metabolomics was analyzed to identify key differential metabolites and pathways. Correlations among clinical, microbial, and metabolomic data were further explored. Results The prevalence of Scardovia wiggsiae (90.6%, P < 0.001), Streptococcus mutans (43.8%, P = 0.006), Streptococcus sobrinus (62.5%, P < 0.001), Ligilactobacillus salivarius (93.6%, P = 0.01) and Candida albicans (56.3%, P < 0.001) were significantly higher in the ECC group. The prevalence of ECC was higher in children with two targeted species present compared with children with one targeted species. Histidine metabolism and branched-chain amino acids degradation were activated in ECC group, while glyoxylate and dicarboxylate metabolism, purine and pyrimidine metabolism were inhibited. Histidine and glutathione metabolism was activated with enrichment of targeted microbial species, while linoleic acid metabolism and biotin metabolism was inhibited. The duration of each toothbrushing was a significant risk factor for ECC experience. Conclusion The prevalence of Scardovia wiggsiae, Streptococcus mutans, Streptococcus sobrinus and Candida albicans is higher in ECC children compared to caries-free children. Oral habits and salivary metabolites also vary between ECC and caries-free children.